Production, fortification, stabilization, and physical-chemical characterization of peanut batter local in Mozambique (Research, Society and Development, 2025)
This investigation aimed to use vitamin A as a fortifying agent and hydrogenated palmitic acid as a stabilizer to fortify, stabilize, and perform physicochemical characterization of peanut butter. The stabilizer and the fortifying agent were manually added to the produced peanut butter and then homogenized. Each formulation: plain (F1), with salt (F2), with sugar (F3), and with a mixture of sugar and salt (F4), was prepared in triplicate, both stabilized and non-stabilized, to measure of the following parameters: moisture, water activity, ash, lipids, proteins, carbohydrates, and metabolizable energy. The results indicated an optimal fortification level achieved at the second and third levels of fortifier addition, and good stability was obtained with a 3% level of stabilizer. Physicochemical analyses yielded the following average results: moisture 1.40%, ash 1.00%, proteins 25.24%, lipids 50.86%, and carbohydrates 21.51%. The average metabolizable energy was 2727.20 kcal/kg. The water activity before the addition of the stabilizer was 0.71, 0.57, 0.54, and 0.53 for formulations F1, F2, F3, and F4, respectively; after stabilization, water activity was 0.13, 0.13, 0.13, and 0.12 for F1F, F2F, F3F, and F4F, respectively. Fortification levels of 29 mg/kg and 43 mg/kg allowed for the maintenance of fortifier contents above the minimum stipulated by Mozambican law for fortified foods.